2014
DOI: 10.3390/rs6054217
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Spatiotemporal Variations of Global Fractional Vegetation Cover Based on GIMMS NDVI Data from 1982 to 2011

Abstract: Fractional vegetation cover (FVC) is an important biophysical parameter of terrestrial ecosystems. Variation of FVC is a major problem in research fields related to remote sensing applications. In this study, the global FVC from 1982 to 2011 was estimated by GIMMS NDVI data, USGS global land cover characteristics data and HWSD soil type data with a modified dimidiate pixel model, which considered vegetation and soil types and mixed pixels decomposition. The evaluation of the robustness and accuracy of the GIMM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(93 citation statements)
references
References 55 publications
2
79
0
Order By: Relevance
“…Before the trend analysis, we computed the serial correlation coefficient according to the Section 3.2.3 of reference [27] and found that only 7.2% of the total area has shown significance at the 5% level and is mainly distributed in the western desert area of study area. Therefore, we think the autocorrelation is negligible.…”
Section: Analysis Of the Causes Of Vegetation Coverage Change In Innementioning
confidence: 99%
See 1 more Smart Citation
“…Before the trend analysis, we computed the serial correlation coefficient according to the Section 3.2.3 of reference [27] and found that only 7.2% of the total area has shown significance at the 5% level and is mainly distributed in the western desert area of study area. Therefore, we think the autocorrelation is negligible.…”
Section: Analysis Of the Causes Of Vegetation Coverage Change In Innementioning
confidence: 99%
“…A trend analysis was used to simulate the annual change trend of FVC for each pixel; the algorithm is shown in reference [26,27].…”
Section: Trend Analysismentioning
confidence: 99%
“…Numerous researchers have used FVC to reveal laws of spatial variation of the surface, to discuss driving factors of change, and to analyze regional ecological transitions [11,[16][17][18]. For example, Wu et al [19] used FVC to estimate the change trend from 1982 to 2011 by GIMMS NDVI data on a global scale. Zhang et al [20] analyzed and appraised the changes in vegetation patterns and revealed a pattern of spatial change in the vegetation coverage of a typical oasis region in the Tarim River Watershed, by producing a map of FVC levels.…”
Section: Introductionmentioning
confidence: 99%
“…These studies are mainly based on including temporal correlation of individual pixels at different resolutions but ignoring spatial dependence among them. Perhaps the most broadly used method for analysing NDVI temporal changes is the non-parametric Mann-Kendall test (see, for example, [11][12][13][14]). When plotting significant changes, a discrete pixel by pixel map of the NDVI trend changes is obtained.…”
Section: Introductionmentioning
confidence: 99%